2017
DOI: 10.1038/s41598-017-10847-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid transfection influences the readout of nonsense-mediated mRNA decay reporter assays in human cells

Abstract: Messenger RNA (mRNA) turnover is a crucial and highly regulated step of gene expression in mammalian cells. This includes mRNA surveillance pathways such as nonsense-mediated mRNA decay (NMD), which assesses the fidelity of transcripts and eliminates mRNAs containing a premature translation termination codon (PTC). When studying mRNA degradation pathways, reporter mRNAs are commonly expressed in cultivated cells. Traditionally, the molecular mechanism of NMD has been characterized using pairs of reporter const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…Expression of the exon-skipped mRNA from the mt19–22FC minigene was 1.3 fold higher than that from the mt19–22 minigene, suggesting that the mt19–22 exon 20-skipped mRNA isoform is only weakly susceptible to NMD (Figure 4A ). It was recently reported that the NMD efficiency of a PTC-containing gene expressed from a plasmid can be variable, depending on the transfection method and cell type ( 32 ). To investigate the regulation of exon 20-skipped IKBKAP isoform mRNA levels by NMD in a more natural context, we used the patient skin fibroblast line GM04899 (Coriell Cell Repository), which was isolated from an individual homozygous for the major FD mutation.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of the exon-skipped mRNA from the mt19–22FC minigene was 1.3 fold higher than that from the mt19–22 minigene, suggesting that the mt19–22 exon 20-skipped mRNA isoform is only weakly susceptible to NMD (Figure 4A ). It was recently reported that the NMD efficiency of a PTC-containing gene expressed from a plasmid can be variable, depending on the transfection method and cell type ( 32 ). To investigate the regulation of exon 20-skipped IKBKAP isoform mRNA levels by NMD in a more natural context, we used the patient skin fibroblast line GM04899 (Coriell Cell Repository), which was isolated from an individual homozygous for the major FD mutation.…”
Section: Resultsmentioning
confidence: 99%
“…CFBE cells provide a native human context for CFTR expression [47] whereas MDCK cells are of mammalian non-human origin but retain epithelial cell machinery for protein trafficking and polarization [4248]. HEK293 stable cell lines are useful for rapid evaluation of mRNA stability and protein processing in a human-derived cell model system that does not polarize [66, 67]. Although heterologous expression systems may not capture features of airway cells from primary nasal or bronchial cultures such as assessment of nasal mucociliary clearance [68], they have been deemed sufficient to approve clinical expansion of drug labels by the FDA [69, 70].…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of this premature stop codon would likely cause nonsense-mediated decay of the mRNA, which might also explain, at least in part, why only small amounts of E3DEL were detected in Caco-2 and HepaRG cells and human liver samples. Our finding in the transiently transfected HEK293T cells that E3DEL-derived mRNA levels were not lower than TV1-or TV2-derived mRNA levels does not rule out this possibility, since nonsense-mediated mRNA decay from transiently transfected constructs was recently reported to be deficient in HEK293 cells (Gerbracht et al, 2017). The lower protein content observed in TV2-transfected cells is likely attributable to instability of the generated protein, which would have a massive loss of 75 amino acids relative to the wild-type protein.…”
Section: Discussionmentioning
confidence: 61%